GEOCHEMICAL MODELING FOR THE ASSESSMENT OF THE CO2 STORAGE POTENTIAL IN THE MESOHELLENIC TROUGH, NW GREECE - Koukouzas, N.; Kypritidou, Z.; Purser, G.; Rochelle, C.A.; Vasilatos, C. (Bulletin of the Geological Society of Greece, 2016)
Sandstone of the Pentalofos formation from the Mesohellenic Trough was examined as a potential reservoir for CO2 sequestration. Experiments were carried out into batch reactors for 6 months by mixing a simplified porewater solution saturated with CO2 (150 bar, 70oC) with crushed sandstone. The sandstone is mainly composed of carbonates, feldspars and quartz, and secondly of clays and phyllosilicates. Chemical analysis of aqueous samples showed an increase in the concentration of dissolved ions as the experiment progressed. Geochemical kinetic models that were constructed using the PHREEQC geochemical code showed that the fluid chemistry is controlled by carbonate and feldspar dissolution, clay and quartz precipitation and cation exchange reactions. The proposed models were also used to estimate the future changes in mineralogy of the sandstone in order to evaluate its suitability as a CO2 reservoir.